Adult Protective Services Perspectives on Responding to Elder Abuse and Serving Clients During the COVID-19 Pandemic. (July 2023) - Elman, Alyssa; Gottesman, Elaine; Makaroun, Lena K.; Chang, E-Shien; Baek, Daniel; Clark, Sunday; Rosen, Tony
The initial COVID-19 pandemic and subsequent public health measures dramatically impacted Adult Protective Services (APS), requiring rapid adjustments. Our goal was to describe challenges for APS and strategies developed to respond. We conducted six focus groups and seven interviews during March–April 2021 using a semi-structured topic guide, with 31 participants from APS leadership, supervisors, and caseworkers in New York City, a community hard hit by the initial COVID surge. Data from transcripts were analyzed to identify themes. Participants identified challenges faced by APS (e.g., clients less willing to engage with APS, inability to perform necessary job tasks remotely, and low staffing levels) as well as strategies APS used in response (e.g., increasing collaboration with other community-based programs and service providers, enabling remote court hearings through technology and in-person facilitation, and ensuring staff had access to personal protective equipment). These findings may inform APS planning for future large-scale societal disruptions.